2018
DOI: 10.1016/j.nmni.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter cloacae harbouring blaKPC-2 and qnrB-1 isolated from a cystic fibrosis patient: a case report

Abstract: We describe the first detection of a KPC-2- and QnrB-producing Enterobacter cloacae from a patient with cystic fibrosis. The blaKPC-2 and qnrB-1 genes were located in a 79.8-kb plasmid. The presence of blaKPC-2 and qnrB-1 genes was determined by PCR and sequencing. Mobilization of plasmid containing blaKPC2 gene was assayed by conjugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…Further, the authors found that the bla KPC gene was detected in 80 % of the isolates, corroborating the data in this study, where we found an occurrence of 88.8 % for the bla KPC gene. These occurrence rates of the bla KPC gene identified in this study highlight the persistence of this gene in K. pneumoniae , and since its detection in 2006 from Recife, Brazil 13 , it remains the main carbapenemase associated with carbapenem-resistant K. pneumoniae samples in several Brazilian states, including Recife-PE 1 , 5 , 32 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Further, the authors found that the bla KPC gene was detected in 80 % of the isolates, corroborating the data in this study, where we found an occurrence of 88.8 % for the bla KPC gene. These occurrence rates of the bla KPC gene identified in this study highlight the persistence of this gene in K. pneumoniae , and since its detection in 2006 from Recife, Brazil 13 , it remains the main carbapenemase associated with carbapenem-resistant K. pneumoniae samples in several Brazilian states, including Recife-PE 1 , 5 , 32 .…”
Section: Discussionsupporting
confidence: 58%
“…The excessive and indiscriminate use of beta-lactam antimicrobials has culminated in the emergence of antibiotic-resistant K. pneumoniae strains and other carbapenem-resistant Enterobacteria 1 , 5 , 6 , 7 . The development of resistance is related to the production of beta-lactamases which is mediated by conjugative plasmids 8 , 9 , 10 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%